Recubrimiento comestible natural con base en Aloe vera como estrategia de conservación de Psidium guajava - García-Mera, George Adalberto; Salas-Macías, Carlos Alfredo; Canales-Torres, Heydi Gwendoline (Revista Científica, 2017)
Global food industry encounters the need for new strategies and technological changes that favor the preservation of fruits. In this sense, coatings have shown great benefits for the industry and consumers. This research has as main objective to evaluate the effect of the application of a natural coating using as a main ingredient Aloe vera in guava, which by its climacteric nature tends to reach senescence quickly in the post-harvest processes, losing quality in very short time. In order to achieve the stated objective, seven treatments to evaluate three doses of Aloe vera (10%, 20% and 30%) mixed with two doses of glycerol (1.5% and 2.5%) were determined. The response variables were: weight loss (loss percentage relative to the weight of fresh fruit), pH of the fruits, total soluble solids (TSS), titratable acidity, presence pathogens defined by total colony forming units (CFU). The best treatment was T5, due to it had the best values in each of the variables analyzed. Such treatment consisted of 30% Aloe vera and 1.5% glycerol. The evaluation concludes that the coating based on Aloe vera and glycerin applied to guava, is able to reduce maturation and managing guava fruit to keep in good condition according to the passage of time.